THE USE OF MATHEMATICAL MODELS FOR THE OPTIMIZATION OF TRANSPORTS FROM THE COMPANY’S LOGISTICS AND OF FORRESTER MODELING TECHNIQUES ON TRAFFIC PROBLEMS - Dorulet GRADINARU; Puiu GRADINARU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2017)
The optimization of transport from the company’s external logistic entails, besides the use of mathematical models based on linear programming, a correlation with the system’s dynamic functioning models. The purpose is minimizing delays in road traffic, thus having the material resources present in time for the production process. The use of Forrester techniques for this optimizes the ratio between the demands of the market for different products made by the company and the means of supplying them.